The effect of toluene sulfonic acid remimazolam on postoperative delirium in elderly patients undergoing painless bronchoscopy - Yan Shi; Lin Zhang; Yujing Diao; Mingqiang Zhao (Scientific Reports)
Abstract Toluene sulfonic acid remimazolam is a novel benzodiazepine that differs from traditional benzodiazepines (BZDs) due to its rapid onset, swift metabolism, and lack of hepatic or renal metabolism, as well as its reduced effects on cardiac and cerebral functions. Despite its potential advantages, clinical experience with this agent remains limited. This study investigated the effect of remizolam on postoperative delirium in elderly patients undergoing painless bronchoscopy. Among elderly patients undergoing routine painless bronchoscopy examinations, 50 cases were included in the remimazolam group, while the other 50 cases were selected as the propofol group. The primary outcome measured was the incidence of delirium on the first, second, third, fifth, and seventh postoperative days. The secondary outcome was the occurrence of adverse events, including hypotension, hypoxia, physical activity, agitation during recovery, dizziness, and nausea/vomiting during the procedure.This study confirmed that no cases of delirium in the remimazolam group, which also demonstrated a significantly lower incidence of adverse events compared to the propofol group (20% vs. 50%, P < 0.05). The results indicated remimazolam provides effective sedation with minimal adverse reactions and is associated with a lack of complications such as postoperative delirium in elderly patients undergoing painless bronchoscopy.